Trinidad y Tobago. Significant achievements 2010-2017 (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
The main activities carried out by the Institute in Trinidad and Tobago are identified, during the period from 2010 to 2017, with respect to the needs and interests of the country, strengthening issues such as biotechnology, good agricultural practices, agrotourism, public policies, biosafety, agribusiness, manufacturing practices, fodder, marketing, post-harvest handling, animal health, sanitation and food safety through the Codex Alimentarius. Likewise, support was provided to improve the handling and processing of agricultural products, risk management and mapping, agro-processing, control of transmitted diseases and resistance to antimicrobials. Finally, technical assistance was provided to women for their inclusion in agriculture, in the trade of products and in the improvement of the value chains of honey, cassava, cocoa, ruminants and goat milk.